1
$\begingroup$

So I read in another thread about involutory functions, he claims for any real numbers $a$ and $b$, the function: $$f(x) = a + \frac{b}{x-a} = \frac{ax + (b-a^2)}{x-a}$$ satisfies $$f(f(x)) = a + \frac{b}{a + \frac{b}{x-a} - a} = a + (x-a) = x$$

And well, I thought I'd give it a try. So I want to find values of $a, b$ and $c$ at which the function below is involutory:

$$f(x) = \frac{x-a}{bx-c}$$

And I of course want to solve for $a, b$ and $c$. Now, I don't consider myself good enough to know in what direction I need to go to solve this.

My attempt was $$f(f(x)) = \frac{\frac{x-a}{bx-c}-a}{b\cdot\frac{x-a}{bx-c}-c} = x$$

$$\iff\frac{\frac{x-a-abx+ac}{bx-c}}{\frac{bx-ba-cbx+c^2}{bx-c}} = \color{red}{\frac{x-a-abx+ac}{bx-ba-cbx+c^2} = x}$$

Now, how would I continue on to find values for $a,b$ and $c$, which satisfy the equation I colored red? By glance I happened to notice that if $a=b=0$ and $c=-1$, the equation is satisfied; but I want to be able to do it algebraically.

Any help is appreciated, thanks.

Edit 1. I was thinking about using a matrix; however I haven't learned about them yet, but I'd be happy to study a solution using them to see if I can get a hang of it.

http://www.wolframalpha.com/input/?i=x+%3D+%28x-a-abx%2Bac%29%2F%28bx-ba-cb*x%2Bc^2%29

$\endgroup$
  • $\begingroup$ FYI: Still looking for an answer that's a little more aligned to my level. $\endgroup$ – B. Lee Oct 6 '14 at 17:24
1
$\begingroup$

Here's a proof from first principles. Suppose $f(x)$ is a Mobius transform i.e. $f(x)=\dfrac{ax+b}{cx+d}$ with $ad\neq bc$ (this prevents $f(x)$ from being a constant map.)

Suppose we want $f(f(x))=x$ for all $x$. In particular, we have $$-\frac{b}{a}=f(f(-b/a))=f(0)=\frac{b}{d}\implies b=0 \text{ or }a=-d$$ and

$$-\frac{d}{c}=f(f(-d/c))=f(\infty)=\frac{a}{c}\implies c=0 \text{ or }a=-d$$

Thus we have two relevant cases:

  • If $a\neq -d$ then $b=c=0\implies f(x)=\dfrac{ax}{d}$ and $1=f(f(1))=f(a/d)=a^2/d^2\implies a=d$. So $f(x)=x$ is just the identity map.

  • If $a=-d$ then $f(x)=\dfrac{ax+b}{cx-a}$. Then $$f(f(x))=f(\dfrac{ax+b}{cx-a})=\dfrac{a(ax+b)+b(cx-a)}{c(ax+b)-a(cx-a)}=\dfrac{a^2+bc}{a^2+bc}x=x$$ is satisfied identically. (Note that $a^2+bc=bc-ad\neq 0$ by assumption, so the cancellation is always valid.) Thus any nontrivial $f(x)=\dfrac{ax+b}{cx-a}$ is an involution.

$\endgroup$
  • $\begingroup$ Ah, you nailed it pretty good. There's few things on my mind now. Most notably, I wonder, how come for $x=0$ we get $ac-a=0$ and not $\frac{ac-a}{c^2-ba-cbx}$. I also tried entering the equation in Wolfram, and they only gave the solution $a=b=0$ and $c=0$, I don't know. I link the Wolfram input in my post. $\endgroup$ – B. Lee Oct 6 '14 at 16:54
  • 1
    $\begingroup$ @XMLParsing: Well, it'd have to be $\dfrac{ac-a}{c^2-ba}=0$ since there's still an $x$ on the bottom :). (That does raise the specter of $c^2=ab$, but that'd imply that the LHS diverges as $x\to 0$ rather than going to zero.) But I think I might add a second proof that goes directly from $f(x)=\dfrac{ax+b}{cx+d}$. $\endgroup$ – Semiclassical Oct 6 '14 at 16:59
  • $\begingroup$ This was a very though problem for me; too many new words in one day. I think I understood about half of what you said, hah. Anyway, thank you for your answer. Edit 1. Saw your edit, I would LOVE another approch, put it in another answer post if you will. That way users won't be confused later on. $\endgroup$ – B. Lee Oct 6 '14 at 17:02
  • 1
    $\begingroup$ We're not assuming that $x=0$ always. We're just checking whether it works for that particular choice, and in that chosen case the $cbx$ term in the denominator is zero as well. If we were doing $x=1$, then the $cbx$ term would matter. @XMLParsing $\endgroup$ – Semiclassical Oct 6 '14 at 19:20
  • 1
    $\begingroup$ @XMLParsing: Oof, your point just penetrated my thick skull. You're right, there is a hole in the first one; I could repair it via an extra case, but that's pretty tedious. The second proof should be waterproof in any regard, so I'm inclined to remove the first attempt altogether. $\endgroup$ – Semiclassical Oct 6 '14 at 19:31
0
$\begingroup$

factorizing your equation we obtain $(c-1)(bx^2-x(c+1)+a)=0$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.